Pengaruh Model Problem Based Learning (PBL) Terhadap Hasil Belajar Matematika SDN 13 Saruaso Timur - Sovia, Dela; Ayu Anatasha, Desti; Safrizal, Safrizal (UNIVERSITAS SERAMBI MEKKAH, 2025)
Understudy learning comes about are the yield of the instructing and learning prepare. One of the issues in learning at school is the moo learning results of understudies. This could be known from the beginning information of the day by day test scores of understudies who are still within the KKM bwah. Numerous variables influence learning results, one of which is the learning model. The Issue Based Learning (PBL) learning demonstrate may be a agreeable learning show that requires understudies to be dynamic and propel understudies so that they can bolster each other and offer assistance each other in acing the subject matter examined. This investigate is an test inquire about with a pretest-posttest plan. After the investigate was carried out, it turned out that the comes about of learning within the course that utilized the PBL 81.14 learning demonstrate were higher than the lesson that utilized the Routine learning demonstrate 76.98. Based on factual tests, 2,4046 and 1,9893 tables were gotten. Since the esteem of the number > ttabel (2.4046 > 1.9893) implies that it can be concluded that Ho is rejected and Ha is acknowledged.